FORMULASI GRANUL EFFERVESCENT EKSTRAK ETANOL 90% BUAH LABU AIR (Lagenaria siceraria) SEBAGAI ANTIOKSIDAN DENGAN VARIASI GAS GENERATING AGENT - Dyera Forestryana; Yunitha Hestiarini; Aristha Novyra Putri (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Water pumpkin (Lagenaria siceraria) is a vegetable that contains secondary metabolites that are beneficial to health. Its use as a vegetable is less attractive to the people so that to increase its utilization, dosage forms are made that can attract public interest, one of which is effervescent granules. Effervescent granules are the most popular dosage form because they can serve in fresh drinks. This study aims to determine the effect of variations in the concentration of acids (citric acid-tartaric acid) and base (sodium bicarbonate) on the physical properties of the formula. The water pumpkin effervescent granules made with various ratios of citric acid, tartaric acid, and sodium bicarbonate consisting of FI (2: 1: 2.5); F II (1: 2: 2,5); F III (2: 1: 3,52); F IV (1: 2: 3,44). The granule made by the wet granulation method. The physical properties of the formula included organoleptic, moisture content, flow properties, compressibility index, pH, solubility time, and acceptability test. Based on the results of the evaluation of physical properties, the granule formula of the water pumpkin effervescent meets the standard requirements with a moisture content of 1.26% -2.26%, flow properties from 6.33 to 7.0 seconds, angle of repose 31.14Ëš-33.69 Ëš, compressibility index 13.61% -17.08%, pH 6.1-7.1 and dissolving time 191-223.33 seconds. Variations of citric acid-tartaric acid and sodium bicarbonate affect the physical properties and taste of the effervescent granules. Based on the acceptability test showed that the panelists liked the water pumpkin effervescent granules in FII.